1,(18)=1+0,(18)
0,(18)=x
18,(18)=100x
18+0,(18)=100x
18+x=100x
18=99x
x=18/99
x=2/11
0,(18)=2/11
1,(18)=1+0,(18) =1+2/11=13/11
2,(27)=7+0,(27)
0,(27)=x
27,(27)=100x
27+0,(27)=100x
27+x=100x
27=99x
x=27/99
x=3/11
0,(27)=3/11
1,(27)=1+0,(27) =1+3/11=14/11
0,(13)=x
13,(13)=100x
13+0,(13)=100x
13+x=100x
13=99x
x=13/99
0,(13)=13/99
2,(23)=7+0,(23)
0,(23)=x
23,(23)=100x
23+0,(23)=100x
23+x=100x
23=99x
x=23/99
x=23/99
0,(23)=23/99
2,(23)=2+0,(23) =2+23/99
Всегда верно неравенство:
(a-1)^2>=0
a^2-2a+1>=0
1. a^2+1>=2a
Аналогично:
2. b^2+1>=2b
Переумножим неравенства 1 и 2:
(a^2+1)(b^2+1)>=2a*2b
(a^2+1)(b^2+1)>=4ab
a^2b^2 +a^2 +b^2 +1 >=4ab
Что и требовалось доказать.